Investigating the relationship between childhood sexual abuse, self-harm repetition and suicidal intent: mixed-methods study. Issue 4 (8th July 2021) - Troya, Maria Isabela; Cully, Grace; Leahy, Dorothy; Cassidy, Eugene; Sadath, Anvar; Nicholson, Sarah; Ramos Costa, Ana Paula; Alberdi-Páramo, Íñigo; Jeffers, Anne; Shiely, Frances; Arensman, Ella
Abstract : Background: Research into the association between childhood sexual abuse (CSA) and self-harm repetition is limited. Aims: We aimed to examine the association between self-harm repetition, mental health conditions, suicidal intent and CSA experiences among people who frequently self-harm. Method: A mixed-methods study was conducted including consecutive patients aged ≥18 years, with five or more self-harm presentations, in three Irish hospitals. Information was extracted from psychiatric records and patients were invited to participate in a semi-structured interview. Data was collected and analysed with a mixed-methods, convergent parallel design. In tandem, the association between CSA and self-harm repetition, suicidal intent and mental health conditions was examined with logistic regression models and independent sample t -test, with psychiatric records data. Thematic analysis was conducted with interview data, to explore CSA experiences and self-harm repetition. Results: Between March 2016 and July 2019, information was obtained on 188 consecutive participants, with 36 participants completing an interview. CSA was recorded in 42% of the total sample and 72.2% of those interviewed. CSA was positively associated with self-harm repetition (odds ratio 6.26, 95% CI 3.94−9.94, P = 0.00). Three themes emerged when exploring participants' CSA experiences: CSA as a precipitating factor for self-harm, secrecy of CSA accentuating shame, and loss experiences linked to CSA and self-harm. Conclusions: CSA was frequently reported among people who frequently self-harm, and associated with self-harm repetition. Identification of patients at risk of repetition is key for suicide prevention. This is an at-risk group with particular characteristics that must be considered; comprehensive patient histories can help inform and tailor treatment pathways.